Associations of the COVID-19 pandemic with the economic status and mental health of people affected by the Fukushima disaster using the difference-in-differences method: The Fukushima Health Management Survey. (June 2021) - Murakami, Michio; Kobayashi, Tomoyuki; Oikawa, Yuichi; Goto, Saori; Momoi, Maho; Takebayashi, Yoshitake; Ohira, Tetsuya; Yasumura, Seiji; Maeda, Masaharu
Abstract: Although the coronavirus disease 2019 (COVID-19) pandemic and relevant preventive measures can affect the economic status and mental health of the public, their effect remains unraveled owing to a limited number of surveys conducted before and during the COVID-19 pandemic. We investigated the association of COVID-19 and relevant measures with multivariate outcomes among people affected by the Fukushima disaster in 2011 using the difference-in-differences (DID) method. We then analyzed the associations between sociodemographic factors and outcomes. We assessed psychological distress, problem drinking, insomnia state, unemployment, household economic decline, and interpersonal problems using three questionnaire surveys administered in 2018, 2019, and 2020. Participants were grouped according to three time periods by dates of voluntary stay-at-home requests (February 26) and the declaration of emergency (April 16) in Japan. The years 2020 and 2019 were regarded as the treatment group and control group, respectively, after confirming that no DIDs were found between 2018 and 2019. We performed regression analyses to identify the risk factors for outcomes. The DIDs were significant for household economic decline after the declaration of emergency, whereas problem drinking significantly improved. No significant DIDs were observed for other mental health outcomes including psychological distress and insomnia state. Absence of counselors was positively and significantly associated with all outcomes in 2020. Overall, people affected by the Fukushima disaster experienced more economic damage after the declaration of emergency during the COVID-19 pandemic but their mental health status did not reduce. Identifying people who have no counselors and providing them with support are emergent requirements to prevent a subsequent mental health decline. Highlights: The economic status and mental health were evaluated after coronavirus disease 2019. We assess the effect in Fukushima residents by the difference-in-differences method. The economic status worsened after governmental restrictions of social activities. The mental health status was maintained after implementing public measures. Lack of counselors was a risk factor for a worsening economy and poor mental health.